If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -1w = 187 Solving 11 + -1w = 187 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1w = 187 + -11 Combine like terms: 11 + -11 = 0 0 + -1w = 187 + -11 -1w = 187 + -11 Combine like terms: 187 + -11 = 176 -1w = 176 Divide each side by '-1'. w = -176 Simplifying w = -176
| 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x | | 2/3x-5=61 | | 672=.08(x) | | 5-3(2x+2)=1-7x | | 1200-1/6 | | 5(x+3)=3x+35 | | 8r-28=6(3r+7) | | b^2=-5b | | 10g+2=2g+102 | | 6(z-4)=30 | | 3412x=18 | | 16^1/3x^3/5 | | 88=(-n+7) | | 7y=16x+30 | | (72/8)*9 | | S^2-6s-10=6 | | q=z-4n/b | | (12-8)+(9)+(25)=34 | | 3f+3w=17.70 | | 4x-4x^2=3 | | 15+p=7 | | 8x-5=9x+15 | | (6/x^5)^-2 | | 16*x^2-16x+3=0 | | 10-2q=-2+q | | .03x+.04(4y)=760 | | Log*4*(x+5)=log*4*(2x-7) | | r+20=16 |